Credit access and college enrollment - Alex Solis (Uppsala University, Department of Economics, 2013)
Does limited access to credit explain some of the gap in schooling attainment between children from richer and poorer families? I present new evidence on this important question using data from two loan programs for college students in Chile. Both programs offer loans to students who score above a threshold on the national college admission test, enabling a regression discontinuity evaluation design. I find that students who score just above the cutoff have nearly 20 percentage points higher enrollment in first, second and third year than students who score just below, which represent relative increases of 100% , 213% and 446% respectively. More importantly, access to the loan program effectively eliminates the family income gradient in enrollment among students with similar test scores.
urn:nbn:se:uu:diva-204400
Keywords: I22; I24; I28; O1; 330; college enrollment; credit constraints; income gap; college dropout; Chile